2012
DOI: 10.1039/c2ja90005j
|View full text |Cite
|
Sign up to set email alerts
|

Atomic spectrometry update. Clinical and biological materials, foods and beverages

Abstract: Amid the traditional development and applications work reported during the period covered by this review, the most obvious identifiable trend is that of downsizing. This is seen with techniques requiring smaller sample sizes or more effective analyte pre-concentration, and with new instrumentation. Procedures for extraction included the use of nanoparticles in various ways and the single-drop methodology with one example exploiting 1-dodecanol, a material that shifts between liquid and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 214 publications
(273 reference statements)
0
18
0
Order By: Relevance
“…Previous Updates 84,85 have referred to the work of Michalke and colleagues in which concentrations of Se in paired serum and CSF specimens were compared to investigate whether there may be positive uptake into neural tissue. Following from the earlier studies, further work looking at Se 86 and Mn 87 in serum and CSF has been reported.…”
Section: Metallomicsmentioning
confidence: 99%
“…Previous Updates 84,85 have referred to the work of Michalke and colleagues in which concentrations of Se in paired serum and CSF specimens were compared to investigate whether there may be positive uptake into neural tissue. Following from the earlier studies, further work looking at Se 86 and Mn 87 in serum and CSF has been reported.…”
Section: Metallomicsmentioning
confidence: 99%
“…Previous Updates 84,85 have referred to the work of Michalke and colleagues in which concentrations of Se in paired serum and CSF specimens were compared to investigate whether there may be positive uptake into neural tissue. Following from the earlier studies, further work looking at Se 86 and Mn 87 in serum and CSF has been reported.…”
Section: Metallomicsmentioning
confidence: 99%
“…It follows on from last year's review 1 and should be read in conjunction with other reviews in the series. [2][3][4][5] This year will be the last time that Mike Hinds will write for the review. His contribution over many years has been very significant and greatly appreciated.…”
mentioning
confidence: 99%